A Rare Case of Extramedullary Relapse of Multiple Myeloma Causing Bowel Obstruction. (11th April 2019) - Bhardwaj, Prarthna V.; Khanna, Shrinkhala; Jawad, Majd D.; Ali, Syed S.
Abstract : Extramedullary myeloma, defined by presence of plasma cells outside the bone marrow, is a rare entity accounting for about 3–9% of all cases. It usually is aggressive with a median survival of <6 months. It is also associated with adverse prognostic factors including 17p deletions and high-risk gene profiles. While common extramedullary sites include bones, there have been several case reports of hematogenous extramedullary myeloma to the liver, lungs, pancreas, breast, skin, and soft tissues. Extramedullary myeloma to the mesentery is a rare entity with only a handful of cases reported. We present a case of 69-year-old man presenting with relapse of multiple myeloma to the mesentery, resulting in bowel obstruction to highlight the various presentations of myeloma.